Stock market and real activity : an empirical study of several Asian countries / Masturah Ma'in, Arifin Md. Salleh and Abd. Ghafar Ismail - Ma'in, Masturah; Md. Salleh, Arifin; Ismail, Abd. Ghafar (Institute of Research, Development and Commercialization (IRDC), 2007)
The objective ofthis study is to investigate the performance ofthe stock market as an indicator to real activity. The evidence ofthis relationship will focus on the sample of data obtained from Malaysia, Japan, Australia, India and Pakistan. The ordinary least square (OLS) and ECM-causality are used to examine the cointegration relationship and causality effect through the sample of data frequency to the related countries. The results show that there is causal-link between stock returns and industrial production index. This particularly exists in Australia, Japan and Malaysia. However, in Pakistan and India, there are no effects traced Therefore, based on the empirical evidence, it clearly shows that the stock market does not predict the real activity in all Asian countries compared to the developed countries in which their stock markets play an important role in predicting the real activity.